Caring for patients with congenital heart disease: a nationwide survey of nurses' educational needs. (2nd January 2022) - Griffiths, Linda; Seaton, Sarah; Lotto, Robyn
Abstract : Background/Aims: Around one in 130 babies are born with some form of congenital heart defect. Advances in treatment have resulted in increasing numbers of these individuals surviving with complex disease; around 90% survive into adult life. In order for these patients to receive high-quality care throughout their lives, it is imperative that nurses are educated appropriately. This study explored the educational needs of nurses who encounter this group of patients. Methods: A survey designed by the British Adult Congenital Cardiac Association was distributed to all congenital heart disease networks in the UK, as well as on social media and via networks and forums for nurses and allied health professionals. The survey took place between 4 June 2020 and 6 July 2020. Responses were analysed using summary statistics. Results: A total of 513 survey responses were received from nurses and allied health professionals. Band 5 nurses reported a higher level of anxiety about caring for patients with congenital heart defect (17.9%) than average for the study population (12.5%). In the previous 2 years, nearly one-third of the band 5 staff had received no training. Respondents who worked in non-congenital heart defect centres reported that learning to manage care for patients with congenital heart defects, manage emergencies and have a simple understanding of the condition should be an educational priority. Local taught study days were identified as the most desirable means of learning. Conclusions: While education within specialist centres appears to be developed and well-embedded, junior nurses (band 5), and particularly those working in non-cardiac units, are being left behind. Easy access information about emergency care and simple descriptions of care requirements would benefit nurses who rarely encounter congenital heart defect patients. Including the fundamentals of care within the nursing curriculum could provide a base from which nurses can develop. Preferences for accredited study sessions support the need for further development of postgraduate education.